Utilization of the Student Engagement Report System in Building a Student Portfolio for Work Readiness in Indonesia - Saiful, Nur Aisyah Qadri; Hakim, Nur (West Science Business and Management, 2025)
This study investigates the utilization of the Student Engagement Report System (SERS) to build student portfolios and its impact on work readiness in Indonesia. Employing a quantitative approach with 200 student samples, data was collected using a Likert scale (1-5) and analyzed with SPSS version 25. The findings revealed significant positive relationships between student engagement, portfolio development, and work readiness. Regression analysis demonstrated that both student engagement and portfolio development significantly contribute to work readiness, with portfolio development showing a stronger influence. The results highlight the potential of SERS to foster educational innovation, enhance student engagement, and support the development of personalized portfolios, ultimately improving graduate employability. These insights provide valuable implications for policymakers and educators aiming to bridge the gap between education and workforce demands.